New Redundant Manipulator Robot with Six Degrees of Freedom Controlled with Visual Feedback - Urrea-Onate, E (IGI Global, 2016)
The design and implementation stages of a redundant robotized manipulator with six Degrees Of Freedom (DOF), controlled with visual feedback by means of computational software, is presented. The various disciplines involved in the design and implementation of the manipulator robot are highlighted in their electric as well as mechanical aspects. Then, the kinematics equations that govern the position and orientation of each link of the manipulator robot are determined. The programming of an artificial vision system and of an interface that control the manipulator robot is designed and implemented. Likewise, the type of position control applied to each joint is explained, making a distinction according to the assigned task. Finally, functional mechanical and electric tests to validate the correct operation of each of the systems of the manipulator robot and the whole robotized system are carried out. © 2017 by IGI Global. All rights reserved.